The propose governance framework for shariah corporation - Zuhairah Ariff, Abd Ghadas; Hartinie, Abd Aziz (2019)
Shariah Corporation has developed rapidly offering a various product and services that comply with the shariah principles. Nevertheless, all the so called shariah corporation was framed under conventional framework beginning from its incorporation as a company up until its corporate governance, and decision’s making process. Such conventional framework does differ from the shariah framework. Hence, it is a need to develop a new framework of governance that can be applied to all shariah corporations. This is mainly because the objective of the conventional and the Islamic Corporate governance is different as conventional corporate governance structure is more focused on the protection of the rights of the stakeholders; while Islamic corporate governance focus on retaining the Islamicity of whole corporation This paper emphasizes that Shari’ah compliance is the core element of shariah corporation and thus Shari’ah governance is an ideal platform to ensure such adherence and thus boost up the level of public confidence in shariah corporation. It is undeniably that, there are few shariah governance codes available nowadays, but, these codes are mainly referred to Islamic financial institution per se. This study looks at the current conventional framework and accordingly, this paper proposes a Shari’ah governance framework to accommodate the shariah corporation. The framework suggests incorporating various fundamental governance principles of organisations. This proposed framework is to strengthen the existing guidelines and reflect a holistic governance system for shariah corporation.